Development and Assessment of a Water-Based Drilling Fluid Tackifier with Salt and High-Temperature Resistance - Yue Gao; Xiaobo Wang; Yun Cheng; Xuan Qi; Hao Yan (Crystals)
A high-temperature-resistant copolymer thickener (DT) was synthesized through free radical polymerization, utilizing monomers such as N-vinylformamide (NVF), divinylbenzene (DVB), and acrylamide (AM) as the primary raw materials. The polymer system’s structure was characterized using FTIR and 1H NMR, while its thermal properties were analyzed through thermogravimetric analysis. The viscosity changes of the polymers were evaluated before and after high-temperature aging at various temperatures. The results indicated that the viscosity retention rate of the thickener DT in the base slurry at 240 °C and 15% NaCl was 87.1%. Additionally, it exhibited varying anti-aging cycles between 200 °C and 240 °C. In a slurry with 25% NaCl, the viscosity retention rate reached 130% at 200 °C. High-temperature and high-pressure rheological tests demonstrated that drilling fluids containing DT exhibit consistent rheological behavior within the temperature range of 150 °C to 180 °C, which aids in stabilizing the viscosity and strength of drilling fluids at elevated temperatures.